Order reduction using improved pole clustering with Pade approximation method for linear system. (2015) - Tiwari, Sharad Kumar; Kaur, Gagandeep
An enhanced pole clustering method is presented that yields linear time invariant-reduced order system. This is accomplished by using the combined benefits of improved Pade approximation method. The applicability of the proposed method for both single and multi-variable linear time invariant systems is verified by solving numerical experiment. Furthermore, the results show that the realised LTI-reduced order system retains stability and steady-state conditions of the original system. The reduced model also exhibits lower integral square error values.